Respuesta a la prueba tuberculínica comparativa en ovinos de establecimientos mixtos de la región norte de la provincia de La Pampa - Castillo, M. (2017)
The situation of bovine tuberculosis in the herds is determined through individual inoculation intradermally of Mycobacterium bovis derivatives. The disease has been reported in sheep, whose production in Argentina is moved from extensive to a more intensified system. Within the framework of the National Plan for the Control and Eradication of Bovine Tuberculosis, it is necessary to incorporate the ovine species, since both bovine and sheep are the hosts of the same pathogen, acting as reservoirs and/or disseminators of the infection for species of productive interest and man. The diagnosis in sheep is made through the comparative tuberculin test, which also surveys for infections such as pseudotuberculosis and paratuberculosis. In La Pampa, there are no data on the presence and prevalence of tuberculosis in this species, nor on the response to the test. The objective of the present study was to analyse the response to the comparative tuberculin test in sheep from mixed farms in the north of La Pampa province and to generate basic information for future work. A total of 234 sheep were examined in 5 production units. 16.66% of the animals were reactive to Avian tuberculin, which is taken as an indication of the para-specific response by other infections, however, it will be necessary to determine the associated pathology. In the present trial, there were not observed any bovine tuberculosis positive sheep indicating that this species is not acting as either reservoir or disseminator of the infection.